(untitled) (Research, Society and Development, 2021)
Foodborne diseases (FBD) present high prevalence worldwide and more than 250 types have been reported. The main agents are Staphylococcus aureus, Escherichia coli, Salmonella and certain parasites. The habit of consuming foods sold in street markets in the city of São Paulo exposes consumers to the risk of acquiring FBD. 25 samples of vinaigrette salad were collected in the central, northern, southern, eastern and western regions of the city of São Paulo, Brazil. The samples were inoculated in selective, enriched culture media and biochemical analyses were performed. Bacterial and fungal growth occurred in all samples. The microorganisms detected were E. coli (64%), Enterobacter (60%), S. aureus (52%), Klebsiella (40%), Proteus sp. (32%), Shigella sp. (28%), Citrobacter sp. (16%), Edwardsiella sp. (12%), Alcaligenes sp. (8%), Serratia sp. (8%), Salmonella sp. (4%), Pseudomonas sp. (4%) and; 72% were positive for aflatoxins. Twelve species were identified, 50% of which can cause FBD. S. aureus and fecal coliforms can cause FBD, while Alcaligenes sp. can cause nosocomial infections and Edwardsiella sp. can cause hepatic abscess, meningitis and septicemia. Aflatoxins may cause mycotoxicoses and liver cancer. Therefore, inspections, and prevention and awareness measures should be reinforced to minimize the risks of contracting FBD from foods sold in street markets in the city of São Paulo.